The Analysis of Positive Politeness Strategies Used by Anies Baswedan in Nationalistic Speech in “Deklarasi Garda Matahari” - Santoso, Dwi; Amaliawati, Shafira (Journal Corner of Education, Linguistics, and Literature, 2024)
Maintaining politeness has an important role in communication. However, using considerate language to communicate respectfully and appropriately is crucial. An investigation into the politeness strategy was carried out in light of these occurrences. In this study, the researcher examined Anies Baswedan, an Indonesian political figure, and her use of politeness strategies, particularly positive politeness. The goals of this study were to identify the positive politeness techniques and the factors that encourage Anies Baswedan to implement them in his nationalistic speech. This study employed a descriptive qualitative research design, and the politeness strategy was analyzed using Brown and Levinson's (1987) theory of politeness strategies. The result of this research showed that there were thirteen utterances representing the eighth positive politeness strategy used by Anies Baswedan in the "Deklarasi Garda Matahari" event. The use of politeness strategies is mostly related to the political atmosphere that is happening in Indonesia.